2021
DOI: 10.1007/s11071-020-06040-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural coupling mechanism in fMRI hemodynamics

Abstract: Neural activity alters with the changes in cerebral blood flow (CBF) and blood oxygen saturation. Despite that these changes can be detected with functional magnetic resonance imaging (fMRI), the underlying physiological mechanism remains obscure. Upon activation of the specific brain region, CBF increases substantially, albeit with 6–8 s delay. Neuroscience has no scientific explanation for this experimental discovery yet. This study proposed a physiological mechanism for generating hemodynamic phenomena from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…The highly nonlinear and complex brain dynamics as well as their various functional expressions are not only related to gene and functional genomics, biology and biochemistry, but also to solid mechanics (McIntyre et al 2001), fluid mechanics (Moore and Cao 2008), dynamics and control (Lu et al 2008a, b). Our research shows that some experimental phenomena in cognitive neuroscience can be reproduced and repeated by mechanical models (Wang et al 2015a;Li et al 2022a), and some experimental data that cannot be explained by neuroscience can also be scientifically explained by our mechanical models (Peng and Wang 2021). We also can use mechanical models to predict new experimental phenomena and new neural mechanisms not found in neuroscience .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…The highly nonlinear and complex brain dynamics as well as their various functional expressions are not only related to gene and functional genomics, biology and biochemistry, but also to solid mechanics (McIntyre et al 2001), fluid mechanics (Moore and Cao 2008), dynamics and control (Lu et al 2008a, b). Our research shows that some experimental phenomena in cognitive neuroscience can be reproduced and repeated by mechanical models (Wang et al 2015a;Li et al 2022a), and some experimental data that cannot be explained by neuroscience can also be scientifically explained by our mechanical models (Peng and Wang 2021). We also can use mechanical models to predict new experimental phenomena and new neural mechanisms not found in neuroscience .…”
Section: Introductionmentioning
confidence: 66%
“…In this research area, we have published a series of research results (Wang et al 2021aYuan et al 2021). Using the large-scale neural energy theory to reveal the neural mechanism of the hemodynamic phenomenon of the brain, it was revealed that neural energy is an important marker of the activity of the nervous system, and energy features contain information about external stimuli and neural responses (Yuan et al 2021;Peng and Wang 2021); using the neural energy theory to attain the biophysical mechanism of the mutual coupling and antagonism between the brain DMN and the working memory network, it can be demonstrated that neural energy can effectively fuse DMN s and cognitive networks to interpret and analyze the spatial information and encoded content contained in complex neural activities (Yuan et al 2021). The computational simulation results are in complete agreement with the experimental data (Piccoli et al 2015;Compte 2000;Wei et al 2012;Hsieh and Ranganath 2014;Karlsgodt et al 2005).…”
Section: Brain Theory: Exploration Of Working Mechanism Of the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies had shown that neural energy theory could be effectively used on different levels of brain networks and their coupling for the construction of global neural brain models and coding (Wang and Zhu 2016 ; Wang et al 2020 ). It has been known that theoretical energy theory could successfully interpret the neural mechanism of brain hemodynamic phenomena (Peng et al 2021 ). Why the amount of data in biological visual system would significantly reduce but not affect the external world visual cognition could also be explained by energy theory (Zhong and Wang 2020 ).…”
Section: Introductionmentioning
confidence: 99%